#### Question

Use elementary column operation C_{2} → C_{2} + 2C_{1} in the following matrix equation :

`([2,1],[2,0])=([3,1],[2,0])([1,0],[-1,1])`

#### Solution

`([2,1],[2,0])=([3,1],[2,0])([1,0],[-1,1])`

Applying C_{2} → C_{2} + 2C_{1}, we get

`([2,5],[2,4])=([3,1],[2,0])([1,2],[-1,-1])`

Is there an error in this question or solution?

Solution Use elementary column operation C2 → C2 + 2C1 in the following matrix equation : ([2,1],[2,0])=([3,1],[2,0])([1,0],[-1,1]) Concept: Elementary Operation (Transformation) of a Matrix.